A Juridical Analysis of Abroad Interfaith Marriage’s Position in Indonesia’s Law - Nandapratiwi, Zalma Afika; Nugraheni, Anjar Sri Ciptorukmi; Maharani, Andina Elok Puri (Interdisciplinary Social Studies, 2022)
The implementation of the registration of interfaith marriages abroad and the Population and Civil Registry Service in Indonesia currently does not exist. However, the Population and Civil Registry Office in Indonesia continues to carry out the registration of interfaith marriages held abroad by carrying out the registration of marriages of different religions through an application to the local District Court for marriage permits for prospective husbands and future wives. The purpose of this study is to determine the position of marriages of interfaith couples held abroad in the legal system in Indonesia and the implementation of registration of interfaith marriages held abroad and at the Population and Civil Registry Office in Indonesia. The study used Normative Juridical research methods. This method was used for research on issues related to the abroad interfaith marriage’s posistion in Indonesia’s law. The materials used as research objects of this approach method use primary, secondary, and tertiary legal materials. The Population and Civil Registry Service in Indonesia continues to carry out the registration of interfaith marriages held abroad by carrying out the registration of marriages of different religions through an application to the local District Court for marriage permits for prospective husbands and future wives with the consequences of various administrative requirements that must be submitted before the District Court grants in accordance with Law Number 23 of 2006 concerning Administration  Residency must be registered with the competent authority in the local country and reported to the republic of Indonesia.